2022
DOI: 10.1155/2022/8346816
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Two Heterogeneous Molecular Subtypes and a Prognosis Predictive Model for Hepatocellular Carcinoma Based on Pyroptosis

Abstract: Hepatocellular carcinoma (HCC) is a worldwide malignant cancer with high incidence and mortality. Considering the high heterogeneity of HCC, clarifying molecular characteristics associated with HCC development could help improve patients’ outcomes. Pyroptosis is a novel form of cell death and is noted to be implicated in HCC pathogenesis whereas its molecular feature in HCC is unclear. Thus, we intended to clarify the molecular characteristic as well as the clinical significance of pyroptosis for HCC. A system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…Interestingly, BAK expression was decreased in colorectal tumors and remained unchanged in most conditions [37], but increased BAK expression was strongly associated with a poor prognosis in patients with non-small cell lung cancer [38], which indicates that the role of BAK is unclear in different types of cancers. Consistent with our results, BAK1 has been identified as a prognostic gene in pyroptosis-related HCC and is associated with persistent hepatitis B virus infectionrelated HCC [39,40]. In this study, we found that the expression of BAK1 was upregulated in the high-risk group compared to the low-risk group.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, BAK expression was decreased in colorectal tumors and remained unchanged in most conditions [37], but increased BAK expression was strongly associated with a poor prognosis in patients with non-small cell lung cancer [38], which indicates that the role of BAK is unclear in different types of cancers. Consistent with our results, BAK1 has been identified as a prognostic gene in pyroptosis-related HCC and is associated with persistent hepatitis B virus infectionrelated HCC [39,40]. In this study, we found that the expression of BAK1 was upregulated in the high-risk group compared to the low-risk group.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, a novel ten-genebased signature was constructed by LASSO Cox regression to predict the OS of CCA. Because the heterogeneity among different patients has been widely reported to in uence the biological mechanisms, management, and pathological features of CCA patients 8 , constructing a prognostic biomarker with high precision and sensitivity as well as validation in an independent cohort is urgently needed to improve prognosis 35 . In our study, the prognostic signature was established and validated in several CCA transcriptome and proteome sequencing datasets with high sensitivity and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…In a variety of clinical and translational studies, DHX9 was confirmed as a prognostic gene for cancers. Recently, Lai et al (17) reported that a total of 12 HCC-associated pyroptosis-related genes (HPRGs) including DHX9 were significantly related to poor survival, and a further five-gene risk model including DHX9 was established for prognostic prediction. As the same HCC, the DHX9-related gene prognostic model was established in gastric cancer and showed superior risk stratification (18).…”
Section: Discussionmentioning
confidence: 99%